Effects of inadequate surface sound speed measurements in multibeam echosounder systems - Mahmud, Mohd. Razali (2007)

(untitled)
In any type of survey work, variation of the characteristics of the medium through which the measurements are made is a challenge, thus; having serious effects on the accuracy of the measurements. In hydrographic surveying, the effects are even greater when using sonar techniques. The single most important acoustical variable in the water is its speed. Average speed of sound in the ocean is 1500m/s. But its precise value in a location is strongly depending on temperature, pressure and salinity of that particular location. These factors changes rapidly in time and space due to various reasons like solar heating, evaporation, precipitation, fresh water inflow etc… and water movements like tides, currents and wave actions. In data acquisition, the collection of these dense sound speed data becomes critical. These inadequate sound speeds create unknown propagation through the water column that adds a major uncertainty to multibeam echosounder (MBES) measurements. There are two types of sound speed measurements made in Multibeam sonars. Surface sound speed (SSS) measured at the face of the transducer and sound speed profile (SSP) through the water column. SSS is used to determine the beam pointing angle and SSP is used to determine the depth and position of each beam. This paper explains the necessity of the surface sound speed in multibeam sonars and effects generated by inadequate SSS measurements using real data from RESON SeaBat 8124 multibeam system. When the vessel roll is significant, the roll modulate the errors induced by erroneous SSS measurements. These errors are illustrated in relation to the IHO standards.